Horta escolar : uma proposta interdisciplinar para os anos iniciais do ensino fundamental - Perotoni, Rejane Armiliato de Campos (My University, 2026)
School gardens are recognized as significant pedagogical tools for science education, as they integrate interdisciplinary content, bringing students closer to environmental, social, and nutritional issues. This study is part of the Master's project in Science and Mathematics Teaching at the University of Caxias do Sul, in the research line "Educational Foundations and Strategies in Science and Mathematics Teaching," based on Freirean principles. The project, developed with an elementary school class in the municipality of Vacaria, RS, aims to investigate how implementing a school garden can foster environmental education, promote healthy eating habits, and raise students' awareness of the importance of sustainable development. The methodology includes using the garden as a space for practical and interdisciplinary learning, addressing topics such as sustainable food production and the relationship between society and nature. The results indicate that the initiative fosters meaningful learning, develops awareness of environmental issues, and encourages behavioral changes aimed at preserving nature and improving quality of life. The educational product produced from this research synthesizes the experiences lived, contributing to the dissemination of educational practices focused on sustainability and the teaching of Science in an integrated and transformative way. [resumo fornecido pelo autor]
Hortas escolares são reconhecidas como ferramentas pedagógicas significativas para o ensino de Ciências, pois integram conteúdos interdisciplinares, aproximando os alunos de questões ambientais, sociais e alimentares. Este estudo faz parte do projeto de mestrado em Ensino de Ciências e Matemática da Universidade de Caxias do Sul, na linha de pesquisa "Fundamentos e Estratégias Educacionais no Ensino de Ciências e Matemática", com fundamentação nos pressupostos freirianos. O projeto, desenvolvido com uma turma do ensino fundamental no município de Vacaria-RS, tem como objetivo investigar como a implementação de uma horta escolar pode fomentar a educação ambiental, promover práticas alimentares saudáveis e sensibilizar os estudantes para a importância de um desenvolvimento sustentável. A metodologia contempla o uso da horta como espaço de aprendizagem prática e interdisciplinar, abordando temas como produção sustentável de alimentos e relações entre sociedade e natureza. Os resultados indicam que a iniciativa favorece aprendizagens significativas, desenvolve a conscientização sobre questões ambientais e estimula mudanças de comportamento voltadas à preservação da natureza e à melhoria da qualidade de vida. O produto educacional produzido a partir desta pesquisa sintetiza as experiências vivenciadas contribuindo para a disseminação de práticas educativas voltadas à sustentabilidade e ao ensino de Ciências de forma integrada e transformadora. [resumo fornecido pelo autor]
Keywords: Educação ambiental; Educação alimentar e nutricional; Horticultura- Educação; Ensino fundamental.; Environmental education; Food and nutrition education; Horticulture - Education; Elementary education